2016
DOI: 10.1097/md.0000000000005069
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of 11 Epstein–Barr virus-associated intrahepatic cholangiocarcinoma at a single center in China

Abstract: To date, only 20 cases of Epstein–Barr virus (EBV)-associated intrahepatic cholangiocarcinomas (IHCCs) have been reported in the literature.Pathology records of IHCC from January 1, 2007 to December 31, 2013 were retrieved from our hospital. Clinical information related to EBV-associated IHCC were also obtained, including gender, age at initial diagnosis, tumor size, tumor–node–metastasis stage, and follow-up duration. Surgically resected stage-matched EBV-negative IHCCs with full follow-up were selected for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…The size of LELCC tumors ranged from 1.2 to 7.3 cm in diameter (mean, 3. 3 cm) [12,18].Clinical symptoms were nonspecifific, usually found incidentally or abdominal fullness and abdominal pain [10]. In our study,EBV were positive in situ hybridization and HBV and HCV were both negative in a Chinese middle-aged woman, Clinical information was similar to previous reports.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…The size of LELCC tumors ranged from 1.2 to 7.3 cm in diameter (mean, 3. 3 cm) [12,18].Clinical symptoms were nonspecifific, usually found incidentally or abdominal fullness and abdominal pain [10]. In our study,EBV were positive in situ hybridization and HBV and HCV were both negative in a Chinese middle-aged woman, Clinical information was similar to previous reports.…”
supporting
confidence: 88%
“…Epidemiology and clinical characteristics: EBV-associated ICC is very rare and can be divided into 3 types: LELC, conventional-type ICC and LELCC on the basis of the tumor cellular differentiation, and host cellular immune responses in the tumors [12].Indicating that LELCC, which was first reported by Jeng et al [13] in 2001, is a rare variant of ICC. Literature reported, EBER in situ hybridisation was positive in 70% of LELCC cases, while conventional cholangiocarcinomas are not associated with EBV infection [13] According to previous studies, 26 cases of LELCC was analyzed, found that 73.1% (19 of 26) patients were EBV-positive [1,8].These results suggested that LELCC is highly associated with Epstein-Barr virus (EBV) infection [14] and EBV infection might promote the development of LELCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EBERs were positive in almost all cases, latency membrane proteins-1 and -2 (LMP1 and LMP2) were negative in eight tested samples, and LMP-related gene showed a 30 bp deletion in two tested cases. 137,138 Thus, similar to nasopharyngeal carcinoma, the expression of EBV-related antigens and tumour genetics might drive the lymphocyte recruitment. Expression of PD-L1 has been studied in LEL-CCA and compared with iCCA, showing a much higher rate in LEL-CCA in both tumour and tumour-infiltrating cells, though the latter were not specifically phenotyped.…”
Section: The Inter Ac Ti On B E T Ween the Immune Sys Tem And The Nmentioning
confidence: 99%
“…Further studies were required to investigate the relation between EBV and LEL-CC. [ 4 ] We observed that the average followed month of EBV positive and negative was, respectively, 42.4 months and 20.4 months, which may show that EBV infection can be protective aspect for LEL-CC. The case we reported was positive for EBV, and the patient had 3 years survival after the first surgery.…”
Section: Discussionmentioning
confidence: 72%